2011
DOI: 10.3892/or.2011.1212
|View full text |Cite
|
Sign up to set email alerts
|

The poly(ADP-ribose) polymerase-1 inhibitor 3-aminobenzamide suppresses cell growth and migration, enhancing suppressive effects of cisplatin in osteosarcoma cells

Abstract: Abstract. pharmacological inhibition of DnA repair pathways has been emerging as an effective tool for cancer treatment. poly(ADp-ribose) polymerase (pArp) is involved in DnA repair and transcriptional regulation and is now recognized as a key regulator of cell survival and cell death. In vitro and in vivo data suggest that pArp inhibitors could be used not only as chemo/radiotherapy sensitizers but also as single agents to selectively kill cancer cells in certain types of tumors. In the present study, we inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…These findings suggest that PARP activation plays a key role in promoting cisplatin-induced renal inflammation and injury. We also demonstrate that PARP inhibition does not interfere with the antitumor activity of cisplatin, in fact it rather promotes it, in a human cancer cell line, which is consistent with results of numerous recent in vitro and in vivo experimental and clinical reports [30, 59], overviewed in [8, 6067]. …”
Section: Discussionsupporting
confidence: 90%
“…These findings suggest that PARP activation plays a key role in promoting cisplatin-induced renal inflammation and injury. We also demonstrate that PARP inhibition does not interfere with the antitumor activity of cisplatin, in fact it rather promotes it, in a human cancer cell line, which is consistent with results of numerous recent in vitro and in vivo experimental and clinical reports [30, 59], overviewed in [8, 6067]. …”
Section: Discussionsupporting
confidence: 90%
“…PARP-1 is a poly(ADP-ribose)polymerase that transfers ADP-ribose groups to target proteins and can thereby alter gene transcription [ 10 ]. To test if poly(ADP-ribose)polymerase activity is required for the regulation of CCR6 expression, we treated human Jurkat T cells, HCT116 cells and Hela cells with a PARP-1 inhibitor, 3-aminobenzamide (3-AB), that inhibits PARP-1 enzymatic activity by competing for the NAD+ binding site on PARP-1 [ 14 ]. Cells were treated with 0, 5 and 10 mM 3-AB for 72 h and analyzed for CCR6 expression by qPCR and Western blot ( Fig 6a and 6b ).…”
Section: Resultsmentioning
confidence: 99%
“…Here, we confirmed a higher PARP1 abundance in the pathogenesis of neointimal hyperplasia in both humans and mice. Recently, emerging evidence shows that PARP1 is involved in various cellular processes, such as inflammatory response, vascular function, cell proliferation and migration, independent of its classic function of DNA repair [ [10] , [11] , [12] , [13] , [35] , [36] , [37] ]. A previous study showed that minocycline suppressed VSMCs proliferation and plaque formation by inhibiting PARP1 and inducing CDK inhibitor p27 expression [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Poly (ADP-ribose) polymerase 1(PARP1) is a nuclear protein that performs DNA repair mainly by catalyzing its own poly ADP-ribosylation and other chromatin-related proteins [ 10 ]. In addition, PARP1 is also involved in a variety of cellular functions, including transcriptional regulation, cell cycle progression, cell migration, inflammation, and energy metabolism [ [11] , [12] , [13] ]. Reactive oxygen/nitrogen species are effective activators of PARP1 due to the ability to damage DNA [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%